Does the Nucleoid Determine Cell Dimensions in Escherichia coli? - Zaritsky, Arieh; Vollmer, Waldemar; Männik, Jaan; Liu, Chenli (Frontiers in Microbiology, 2019)
Bacillary, Gram-negative bacteria grow by elongation with no discernible change in width, but during faster growth in richer media the cells are also wider. The mechanism regulating the change in cell width W during transitions from slow to fast growth is a fundamental, unanswered question in molecular biology. The value of W that changes in the divisome and during the division process only, is related to the nucleoid complexity, determined by the rates of growth and of chromosome replication; the former manipulated by nutritional conditions and the latter—by thymine limitation of thyA mutants. Such spatio-temporal regulation is supported by existence of a minimal possible distance between successive replisomes, so-called eclipse that limits the number of replisomes to a maximum. Breaching this limit by slowing replication in fast growing cells results in maximal nucleoid complexity that is associated with maximum cell width, supporting the notion of Nucleoid-to-Divisome signal transmission. Physical signal(s) may be delivered from the nucleoid to assemble the divisome and to fix the value of W in the nascent cell pole.